Acceptance and Continuation of Immediate Postpartum LARC: Experiences From a Texas Hospital [12A]. (May 2017) - Huff, Cristina Wallace; Holcombe, Sara; Duret-Uzodinma, Jenny; Dillaway, Chloe; Hopkins, Kristine; Potter, Joseph E.
Abstract : INTRODUCTION: Lyndon Baines Johnson Hospital in Houston, Texas began offering immediate postpartum placement of long-acting reversible contraception (LARC) in June 2014. We aimed to assess patient demand for this service, along with continuation and satisfaction at 3 and 6 months after delivery. METHODS: We conducted a cohort study of 199 postpartum women who delivered at this hospital. Publicly insured women aged 18-44 who delivered a healthy singleton, and wanted to delay childbearing for 24 months were eligible. Interviews were conducted face-to-face following delivery and by telephone at 3 and 6 months. Women receiving LARC postpartum, were asked about their continued use and satisfaction. RESULTS: Twenty-four women (12%) had an IUD placed immediately following delivery, and 46 (23%) had an implant placed before discharge. Forty-two (21%) had a sterilization before discharge, and 15 (8%) received an injectable. Another 10 participants (5%) said they would have accepted immediate postpartum placement of LARC, but it was not placed. Among the 170 women for whom we had complete follow-up data through 6 months, 62 were using LARC at baseline. 59 were using LARC at 3 months and 6 months. Two implants and one IUD were removed, and one IUD expelled. Of women continuing on LARC, 68% were very satisfied, and 21% somewhat satisfied. CONCLUSION: Acceptance of immediate postpartum LARC among low-income, predominantly Hispanic women is high. Continuation and satisfaction were also high, indicating that the Texas Medicaid rule change permitting reimbursement for postpartum LARC that went into effect in January 2016 could be of great benefit.